2022
DOI: 10.1021/acs.estlett.2c00472
|View full text |Cite
|
Sign up to set email alerts
|

UV 222 nm Emission from KrCl* Excimer Lamps Greatly Improves Advanced Oxidation Performance in Water Treatment

Abstract: KrCl* excimer lamps emitting at 222 nm hold potential for enhancing ultraviolet (UV)-based advanced oxidation efficiency. Experiments were conducted in both ultrapure water and groundwater comparing low-pressure UV (LPUV) and KrCl* excimer lamps, with two different radical promoters [hydrogen peroxide (H 2 O 2 ) and nitrate (NO 3 − )]. Compared to that of conventional LPUV/H 2 O 2 , the steady-state hydroxyl radical (•OH) concentration achieved in the KrCl*/NO 3− UV/AOP was 13.1 times greater while that for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 61 publications
0
42
0
Order By: Relevance
“…Radical yields in the UV 222 /Cl-cyanurates AOP were promoted in the synthetic swimming pool water compared to deionized water, suggesting that water matrix components (e.g., dissolved organic matter, nitrate, and carbonate) might have significant impacts on UV 222 -driven AOPs. 24 Our calculation results based on the molar absorption coefficients and innate quantum yields suggest that the radical yields in the UV/chlorine AOP can theoretically be improved by switching the UV wavelength from 254 to 222 nm, but more experimental evidence needs to be collected to verify this anticipation. The direct UV 222 photolysis of micropollutants could also be promising at the UV fluence that is commonly used in UV-AOPs (e.g., 400− 1000 mJ cm −2 ), 11,66,67 because (1) the energy of UV photons at 222 nm (5.39 × 10 5 J Einstein −1 ) is higher than the bond dissociation energy of many chemical bonds, including C−F, N�N, and O�O bonds; 68 and (2) many micropollutants have high molar absorption coefficients (e.g., tryptophan, 69 bisphenol A, 31 and 4-methycatechol 70 ) at 222 nm.…”
Section: Model Establishment and Prediction On Phmentioning
confidence: 91%
See 2 more Smart Citations
“…Radical yields in the UV 222 /Cl-cyanurates AOP were promoted in the synthetic swimming pool water compared to deionized water, suggesting that water matrix components (e.g., dissolved organic matter, nitrate, and carbonate) might have significant impacts on UV 222 -driven AOPs. 24 Our calculation results based on the molar absorption coefficients and innate quantum yields suggest that the radical yields in the UV/chlorine AOP can theoretically be improved by switching the UV wavelength from 254 to 222 nm, but more experimental evidence needs to be collected to verify this anticipation. The direct UV 222 photolysis of micropollutants could also be promising at the UV fluence that is commonly used in UV-AOPs (e.g., 400− 1000 mJ cm −2 ), 11,66,67 because (1) the energy of UV photons at 222 nm (5.39 × 10 5 J Einstein −1 ) is higher than the bond dissociation energy of many chemical bonds, including C−F, N�N, and O�O bonds; 68 and (2) many micropollutants have high molar absorption coefficients (e.g., tryptophan, 69 bisphenol A, 31 and 4-methycatechol 70 ) at 222 nm.…”
Section: Model Establishment and Prediction On Phmentioning
confidence: 91%
“…This hypothesis can be supported by a recent study which reports that the steady-state concentration of hydroxyl radical (HO • ) normalized by the incident fluence rate in the UV/H 2 O 2 AOP is 9.4 times higher at 222 nm than 254 nm in deionized water and 3.7 times higher in groundwater. 24 Sodium dichloroisocyanurate (NaCl 2 Cy) is a solid form of chlorine that is widely used in treating both swimming pool water and drinking water in many countries (e.g., the United States and New Zealand). 32−37 It is simpler to handle than liquid and gaseous forms of chlorine and can be stored for years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, UV photolysis of nitrate generates radicals (see key chain reactions in Table S1) and the radical yields highly depend on the irradiation UV wavelength . A recent study reported that the yield of HO • generated from nitrate photolysis can be greatly improved by switching the UV wavelength from 254 to 222 nm, but whether the generated HO • can contribute to the inactivation of microorganism and compensate the inner filter effect of nitrate remain unknown. In addition to HO • , reactive nitrogen species (RNS) such as nitrogen oxide radical (NO • ), nitrogen dioxide radical (NO 2 • ), and peroxynitrite (ONOO – ) may also be generated from Far-UVC photolysis of nitrate, , but the concentrations of those RNS and whether they contribute to the inactivation of microorganism remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The molar absorption coefficient (ε) of H 2 O 2 at 222 nm (ε 222 = 99 M –1 ·cm –1 ) is 5.4 times higher than that at 254 nm (ε 254 = 18.5 M –1 ·cm –1 ), while the quantum yield (Φ) is similar at the two wavelengths (Φ 222 = 1.1 ± 0.1; Φ 254 = 1.15 ± 0.05). Hence, the fluence-normalized steady-state concentration of hydroxyl radical by KrCl* excilamps was reported to be 9.4 times higher than that by LPUV . Therefore, the AOP with H 2 O 2 at 222 nm increased the degradation of 4-chlorobenzoic acid and methylene blue by 9 and 3 folds, respectively, compared to LPUV/H 2 O 2 at similar conditions.…”
Section: Introductionmentioning
confidence: 99%